A Novel β-Glucosidase From Chryseobacterium scophthalmum 1433 for Efficient Rubusoside Production From Stevioside - Yan, Zhenxin; Cao, Xueting; Yang, Xiao; Yang, Shida; Xu, Li; Jiang, Xukai; Xiao, Min (Frontiers in Microbiology, 2021)
As a natural sweetening and solubilizing agent, rubusoside has great potential in the application of healthy beverages and pharmaceuticals. However, the direct extraction and purification of rubusoside from raw materials is inefficient. In this work, a novel β-glucosidase (CsBGL) was obtained from Chryseobacterium scophthalmum 1433 through screening of the environmental microorganisms. CsBGL markedly hydrolyzed sophorese (Glcβ-1,2Glc) and laminaribiose (Glcβ-1,3Glc), but for steviol glycosides, it only hydrolyzed the C-13/C-19-linked sophorese, instead of the C-13/C-19-linked Glcβ1-2[Glcβ1-3]Glc trisaccharide and Glcβ1-monosaccharide. It efficiently hydrolyzed stevioside (240 g/L) to produce rubusoside (99% yield) at 47.5 °C for 70 min. Even using a crude steviol glycosides extract (500 g/L) containing ~226 g/L stevioside as the substrate, CsBGL could also converted stevioside to rubusoside (99% yield) at 47.5 °C for 2 h, in which the rubusoside concentration increased from the initial 42 g/L to the final 222 g/L. These results reveal that CsBGL would be a promising biocatalyst for the industry-scale production of rubusoside from stevioside or/and the crude steviol glycosides extract.